The midpoint is given by finding the average x-value and the average y-value, thus the formula would be:
M = ( (x1 + x2)/2, (y1 + y2)/2 ), where (x1, y1) and (x2, y2) are two points on the graph
1. We have two points here, the origin - ie. (0, 0) - and A(18, -6). Thus, using the formula above for the midpoint we get:
M = ( (0 + 18)/2, (0 + (-6))/2 )
M = (18/2, -6/2)
M = (9, -3)
2. Using the same approach, we can find the midpoint for this question using the points J(-9, 5) and K(21, -7):
M = ( (-9 + 21)/2, (5 + (-7))/2 )
M = (12/2, -2/2)
M = (6, -1)